Financing the transition? Taking the temperature of European banks' corporate loan books a pilot study on banks' alignment with the temperature target of the Paris Agreement - Raffaele Passaro; Benno Schumacher; Hannah Helmke; Jacopo Pellegrino; Elnaz Roshan (European Banking Authority (EBA), 2024)
The Paris Agreement requires policy makers to keep the increase in global average temperature well below 2êC above pre-industrial levels, while pursuing efforts to limit the increase to 1.5êC. Furthermore, it demands finance flows to be consistent with pathways towards low greenhouse gas emission technologies. While prudential supervisory authorities so far primarily focussed on assessing banks' resilience to climate-related financial shocks from a risk-oriented viewpoint, e.g. based on dedicated climate stress tests, we argue in this paper for a complementary perspective beyond prudential supervision, namely banks' own contribution to global warming through their financing of climateharmful activities. This perspective becomes especially relevant considering the prospective reporting on double materiality according to the EU Corporate Sustainability Reporting Directive (CSRD). With the objective of the Paris Agreement being defined in terms of degrees Celsius, we examine banks' alignment with the temperature target by quantifying the implied temperature rise of banks' (non-SME) corporate loan books. To that end, we propose an innovative alignment methodology, leveraging on the so-called X-Degree Compatibility (XDC) Model developed by rightê, which we apply on granular exposure-level information collected from selected EU banks. According to our findings, the average implied temperature rise of banks' (non-SME) corporate loan portfolios ranges between 3.7êC and 4.1êC, depending on the aggregation methodology. While we observe some heterogeneity across banks, none of them is on a pathway compatible with the agreed target. Additionally, we show that the implied temperature rise as per our methodology can also serve as proxy for transition risk, thereby combining the twofold objective from a double materiality perspective in a single metric.
Keywords: G21; G28; Q54; Q58; 330; EU banks; Paris Agreement; portfolio alignment; climate transition; financed emissions; implied temperature rise